Design Technology of Large-scale Spiral Wound Heat Exchanger in Refinery Industry. (2015) - Chen, Y.D.; Chen, X.D.; Jiang, H.F.; Chen, C.G.; Zhang, X.A.
Abstract: Due to its excellent heat transfer property, good adaptability to variable loads and operation reliability, large-scale spiral wound heat exchanger (SWHE) has a bright application prospect in the refinery industry of China. With respect to the large-scale hydrocracking unit, both the new heat transfer process and the SWHE design technology are analyzed. As to the design of heat transfer process, high pressure SWHE instead of traditional thread locking ring heat exchanger (TLRHE) is employed, which reduces the number of reaction furnaces and obtains remarkable energy-economizing effect. As to the design innovation of high pressure SWHE, such contents as the structure style, adaptability of whole structure, requirement of material selection, structure of Ni-base alloy butt weldment, design calculation of main structure, technology requirement of high pressure finish-rolling heat exchange tube and design specification of the minimum center tube etc. are discussed. In China, the large-scale refinery SWHE with area larger than 10000m2 can be produced now, and abundant experience has been accumulated in the design technology. However, there is still a certain gap between our country and the advanced countries in Europe and America in such aspects as the material variety of SWHE, the diversity of heat exchange tube specification, the application of numerical simulation technology in design and the inspection and repair technology of high pressure SWHE etc.